Emergence of pandemic 2009 influenza A H1N1, India - Choudhry, Archana (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND & OBJECTIVES: Pandemic H1N1 caused deluge of cases from 74 countries and prompted World Health Organization to raise warning to phase 6. The present study was conducted on throat and nasal swab samples received and tested at National Centre for Disease Control, Delhi, India during 2009-2010 to collect epidemiological and clinical information on positive cases. METHODS: Throat and nasopharyngeal swabs from category C influenza A H1N1 patients during May 2009-September 2010 along with their clinico-epidemiological details were collected from identified hospitals from Delhi and other States. Samples were tested by Real time reverse transcriptase PCR using primers and probes developed at CDC, Atlanta for four influenza target genes. RESULTS: A total of 33,751 samples, both throat and nasal swab samples from each patient were tested for H1N1 influenza virus, of which, 7943 (23.5%) were positive for pandemic influenza A H1N1 and 3759 (11.1%) were positive for influenza A (seasonal flu). Maximum number of positive cases (N=2792, 35.1%) were from 20-39 yr age group, comprising 1790 (22.5%) males and 1182 (14.8%) females. Only 2620 (33%) positive cases were close contact of influenza A H1N1 positive patient. Majority cases presented (N=2792, 35.1%) with fever 7005 (88.1%), followed by 6133 cases (77.2%) exhibiting fever and cough, 377 (4.7%) complained of fever, cough, nasal catarrh and 362 (4.5%) cases had fever with shortness of breath. INTERPRETATION & CONCLUSIONS: The study showed a peak of cases of pandemic influenza A H1N1 in December 2009 and indicated predominance of H1N1 positive cases among 20-39 yr age group and among males compared to females.